Dose‐dependent effect of androgen deprivation therapy for localized prostate cancer on adverse cardiac events. (22nd July 2015) - Schmid, Marianne; Sammon, Jesse D.; Reznor, Gally; Kapoor, Victor; Speed, Jacqueline M.; Abdollah, Firas A.; Sood, Akshay; Chun, Felix K.‐H.; Kibel, Adam S.; Menon, Mani; Fisch, Margit; Sun, Maxine; et al.
Abstract : Objectives: To investigate the dose‐dependent effect of androgen deprivation therapy (ADT) on adverse cardiac events in elderly men with non‐metastatic prostate cancer (PCa) stratified according to life expectancy. Patients and Methods: A total of 50 384 men diagnosed with localized PCa between 1992 and 2007 were identified within the Surveillance, Epidemiology, and End Results registry areas. We compared those who received ADT within 2 years of PCa diagnosis with those who did not, calculated as monthly equivalent doses of GnRH agonists (<8, ≥8 doses), or orchiectomy. Men were further stratified according to life expectancy (<5 years, 5–10 years and >10 years). Adjusted Cox hazard models assessed the risk of new‐onset coronary heart disease (CHD), acute myocardial infarction (AMI), sudden cardiac death (SCD) and cardiac‐related interventions, as well as any of these events. Results: Overall, patients receiving GnRH agonists were more likely to experience a cardiac event, with the most pronounced effect among those receiving ≥8 doses (hazard ratio [HR] <8 doses: 1.13, 95% confidence interval [CI] 1.09–1.16, and HR ≥8 doses: 1.18, 95% CI 1.14–1.22; both P < 0.001). The effect of prolonged (≥8 doses) GnRH agonist use on cardiac events was sustained across all strata of life expectancy; however, there was no effect among men with a life expectancy of <5 years and when use of GnRH agonists was limited to <8 doses (HR 0.99, 95% CI 0.67–1.46; P = 0.964). The use of GnRH agonists was associated with a higher risk of CHD (HR <8 doses: 1.13, 95% CI 1.09–1.17 and HR ≥8 doses: 1.17, 95% CI 1.13–1.21; both P < 0.001). Conversely, the use of GnRH was generally not associated with an increased risk of AMI or SCD, except for men who received ≥8 doses of GnRH agonists and had a life expectancy of ≥5 years, who were at a significantly higher risk of SCD (HR for life expectancy 5–10 years: 1.19, 95% CI 1.06–1.33; P = 0.003 and HR for life expectancy >10 years: 1.16, 95% CI 1.04–1.29; P = 0.006). Finally, orchiectomy was not associated with overall cardiac events, AMI or SCD, and was protective with regard to cardiac‐related interventions (HR 0.78, 95% CI 0.68–0.90, P = 0.001). Conclusion: Exposure to ADT with GnRH agonists is associated with an increased risk of cardiac events in elderly men with localized PCa and a decent life expectancy. Clinicians should carefully weigh the risks and benefits of ADT in patients with a prolonged life expectancy. Routine screening and lifestyle interventions are warranted in at‐risk subpopulations treated with ADT.